Serum cystatin C as a potential biomarker for generalized acetylcholine receptor antibody-positive myasthenia gravis - Dingxian He; Huahua Zhong; Lei Jin; Ran Chen; Zongtai Wu; Rui Zhao; Xiao Huan; Chong Yan; Jie Song; Jianying Xi; Chongbo Zhao; Shanfeng Zhu; et al. (Frontiers in Immunology)
ObjectiveTo identify new metabolic biomarkers associated with myasthenia gravis (MG).MethodsWe analyzed 285 potential metabolic molecules from UK Biobank (UKB) for MG patients and identified elevated serum cystatin C (Cys-C). Validation was performed using laboratory data, ELISA, and clinical information from Chinese (CHN) acetylcholine receptor antibody (AChR-Ab) positive generalized MG (gMG) cohorts. We assessed cytokines/chemokines/complements and peripheral blood T lymphocytes using Luminex assays and flow cytometry. MG-relevant scores including myasthenia gravis activities of daily living score (MG-ADL) and quantitative myasthenia gravis score (QMG) were prospectively collected and retrospectively analyzed. The correlations between serum Cys-C and the ratio of T helper 1 (Th1)/Th2 were assessed.ResultsSerum Cys-C levels were significantly elevated in MG patients compared to healthy controls in both UKB cohorts and Chinese MG cohorts (CHN) (UKB: 0.99 ± 0.20 vs. 0.86 ± 0.12 mg/L, p = 2.26E-41; CHN: 1.08 ± 0.30 vs. 0.87 ± 0.13 mg/L, p = 4.83E-08). Higher serum Cys-C levels were found in MG patients with high disease burden, as stratified by MG-ADL score. Serum Cys-C correlated with MG scores, including QMG (R = 0.40, p = 3.90E-03) and MG-ADL scores (R = 0.42, p = 2.40E-03). The ratio of Th1/Th2 correlated well with the serum Cys-C (R = 0.29, p = 3.10E-02).ConclusionsSerum Cys-C levels were significantly elevated in AChR-Ab positive gMG patients and correlated with disease severity and Th1/Th2 ratio, suggesting its potential as an efficient biomarker for predicting the clinical severity of MG. Future prospective cohort studies with a large sample size are expected to validate these findings.